Mucormycete infection or colonisation: experience of an Australian tertiary referral centre. Issue 5 (9th February 2016) - Langford, S.; Trubiano, J. A.; Saxon, S.; Spelman, D.; Morrissey, C. O.
Summary: Mucormycosis is associated with significant morbidity and mortality. We reviewed patients with mucormycete isolated at Alfred Health, Australia. A retrospective review of 66 patients with mucormycete(s) identified, between 1 April 2008 and 30 June 2014. Baseline demographic, microbiological, radiological, treatment/outcome data were recorded. Site of isolation was sinopulmonary in 77% and skin/soft tissue in 21%. A total of 32% of cases were proven‐IFD, 12% probable‐IFD and 56% were defined as no‐IFD (or colonisation). Rhizopus spp. was identified in 48%. Comparing probable/proven‐IFD with no‐IFD/colonisation, more patients were postallogeneic stem cell transplantation (28% vs. 0%, P < 0.01) and were receiving immunosuppressive therapy (59% vs. 24%, P < 0.01) including prednisolone >20 mg daily (24% vs. 5%, P = 0.04). A total of 93% of patients with proven/probable IFD received treatment while 30% of no‐IFD/colonisation were treated. A total of 72% of patients with proven/probable IFD and 92% of those with colonisation had no further mucormycete isolated. Thirty day mortality was higher in the proven/probable‐IFD cohort (24%) compared with no‐IFD/colonisation (3%) ( P = 0.02). Mucormycosis remains uncommon, with 56% of cases not associated with clinical infection. Immunosuppressive therapy remains strongly associated with mucormycosis. Mortality remains high in those with proven/probable IFD.